Análisis situacional de la oferta de la carrera de enfermería de la Universidad Nacional de Chimborazo noviembre 2017-febrero 2018 - Sánchez Reyes, Mayra Tatiana (2018)
The objective of the research was to determine the actual situation of the Nursing Career offered by the National University of Chimborazo, for which it was made a descriptive, cross-sectional study with a mixed approach. The population considered for this project was 40 professors from the career, but only 35 wanted to participate, who have third and fourth level academic training. For the situational analysis was taken the study of variables based on dimensions of superior education: academic, social and environmental, through them was obtained the information related with the most relevant aspects within the sustainable dimensional field. The results of the research according to the professors' criteria were: the methodology teaching-learning used with most frequently is the master class, the evaluation technique usually applied is the written tests; the projects of the last two years of Linkage with the society have been assessed as quasi-satisfactory and that of satisfactory qualification; on the other hand about the laboratory or simulation centers, it consider that they have a basic equipment; the professors answered that the students contribute to the resolution of problems in pre-professional practices. The study of the criteria grouped in the dimensions of superior education facilitated the analysis of the variables and the results of the research provided information to permanently to improve the academic processes and curricular adjustment.